(untitled) - McBurney, Donald H (Belmont, CA, 2010)
This book provides readers with a scientific approach to understanding the field of psychology. The text's logical, step-by-step coverage is the result of decades of author experience, and includes all of the stages of the research process: selecting the project, searching for literature, choosing a protocol, and getting published. RESEARCH METHODS also presents the reader with problems from psychological literature, in order to examine how real-life psychology professionals design and conduct effective research.
Keywords: Psychology, Experimental,Psychology,Tâm lý, nghiên cứu thực nghiệm,Tâm lý; Methodology,Research,Methodology,Phương pháp luận,Nghiên cứu,Phương pháp luận